In-Memory Data Rearrangement for Irregular, Data-Intensive Computing. - Lloyd, Scott; Gokhale, Maya (Computer (00189162), 2015)
The data rearrangement engine (DRE) performs in-memory data restructuring to accelerate irregular, data-intensive applications. An emulation on a field-programmable gate array shows how the DRE could improve speedup, memory bandwidth, and energy consumption on three representative benchmarks.